PREDICTORS OF SUSTAINED RESPONSE TO INTERFERON-BASED THERAPY IN CHRONIC HEPATITIS B - Deian Jelev; Krasimir Antonov; Aneta Ivanova; Zahariy Krastev (Peytchinski Publishing, 2011)
Objective: IFN-based therapy induces long-term remission in ~20% of CHB-patients. Identification of predictors of treatment response can facilitate the clinical decision. Methods: 168 CHB-patients treated with IFN-based therapy were studied. Predictors of end-of-treatment response (ETR) and sustained response (SR) one-year post therapy were identified by non-parametric chi-square test and correlation analysis. Results: Low baseline HBV DNA (<50,000,000 cp/ml) and high ALT level (>4xULN) were independent predictors of ETR. Low viral load was stronger predictor than high ALT level. If both factors coexist the probability of ETR was 92%. In HBeAg-negative subjects SR correlates significantly with age below 40 years, evidence of early viral response at 3rd month, fibrosis stage F<3 (METAVIR) and prolongation of treatment duration. HBeAg-seroconversion up to 6-month post-therapy was the strongest predictor of SR in HBeAg-positive patients.Conclusion: More favorable results could be achieved by pretreatment selection according to patients' age, baseline viral load, ALT and liver fibrosis. Extension of IFN-treatment in responders may enhance the SR rate.